LAGUAI- Artificial Intelligence Song Composer - Salavamani, Uthayasurian (2021)
Artificial intelligence can be implemented in song composing. This will make the music composers to be more easier to compose the song, including Song lyrics, music and the singer as well. This system will not require the real life singers as well and we can use virtual singer to compose the song.